Analysis of Compound Words in News about the Sumatra Flood Survivors Battle Mud,Trauma - Firmansyah, Arjun; Valentina, Putri; Indriyani, Rohmatin; Sari, Eny Maulita Purnama (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the use of compound words in English-language news reports reporting on the conditions of flood survivors in Sumatra, particularly in describing their struggles with mud, environmental damage, and post-disaster psychological trauma. The purpose of this study is to identify the structural forms, classification types, and semantic functions of compound words used in journalistic discourse on natural disasters. The data source is online news articles from international media published after the floods in Sumatra. This study uses a qualitative descriptive method with a morphological approach, based on the theory of compounding and media discourse analysis as developed in recent linguistic studies (Brown Lee, 2025; Ahmed, 2025). Data were collected through text observation techniques and systematic recording, then analyzed by grouping compound words based on their formation patterns, such as noun + noun, adjective + noun, and verb + noun, and interpreting their meaning in the context of the news. The results of the analysis show that compound words have a strategic role in conveying information efficiently and expressively, especially to represent the physical and psychological impacts of disasters, for example flood survivors, mud-damaged houses, and post-disaster stress. In addition to functioning informatively, compound words also strengthen the emotional and persuasive dimensions of news texts, thereby helping readers build a deeper understanding of the conditions of the victims. This study is expected to enrich the study of morphology and media discourse analysis, as well as become a reference for researchers and language learners